Detailed assessment of the distribution of Astrocaryum sect. Huicungo (Arecaceae) in Peru - Kahn, Francis (2011)
Detailed distribution of Astrocaryum sect. Huicungo (Arecaceae) in Peru is presented and discussed. Twelve out of the 15 species that compose this section are found in the Peruvian territory from North to South in the eastern Andean foothills and western Amazonian lowlands. All these species have a parapatric distribution, except for Astrocaryum macrocalyx and A. urostachys, which share a very limited area. Limits of distribution areas may be related to geographical, geomorphological and ecological barriers (river, geological rising, soil drainage). In some cases, however, the contact between species is almost contiguous; no natural barrier could be detected in the field.